2003
DOI: 10.1142/s0218348x0300163x
|View full text |Cite
|
Sign up to set email alerts
|

Fractality of Monthly Extreme Minimum Temperature

Abstract: Interest in climate change has increased over the last 30 years due largely to global predictions associated with the greenhouse effect, which appear to lead to a substantial increase in planetary temperature. Implications of such results have led many scientists to examine climatic records from different regions of the world in order to understand temperature behavior. However, many researchers have noted that changes in temperature variability are also important in determining the future temperature distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
9
0
6
Order By: Relevance
“…It should be noted, however, that the results of this study coincide with those reported by other researchers for other localities and regions in the sense that downward and upward trends are presented in both types of temperatures. This implies, then, that our results are evidence that there may be local and regional trends that run counter to the global trend, as previously pointed out by Valdez-Cepeda et al (2003a). tados presentados en esta contribución coinciden con lo reportado por otros investigadores para otras localidades y regiones en el sentido de presentar tendencias de decremento e incremento en ambos tipos de temperaturas.…”
Section: Trendssupporting
confidence: 83%
See 4 more Smart Citations
“…It should be noted, however, that the results of this study coincide with those reported by other researchers for other localities and regions in the sense that downward and upward trends are presented in both types of temperatures. This implies, then, that our results are evidence that there may be local and regional trends that run counter to the global trend, as previously pointed out by Valdez-Cepeda et al (2003a). tados presentados en esta contribución coinciden con lo reportado por otros investigadores para otras localidades y regiones en el sentido de presentar tendencias de decremento e incremento en ambos tipos de temperaturas.…”
Section: Trendssupporting
confidence: 83%
“…En las series de ambas temperaturas, registradas en Guanaceví, se apreció la frecuencia de 20 años, lo cual indica que posiblemente están influidas por el ciclo magnético del Sol (Mendoza et al, 2001;Valdez-Cepeda et al, 2003a).…”
Section: Discussionunclassified
See 3 more Smart Citations